Improving the Quality of Health Care for Mental and Substance-Use Conditions - Institute of Medicine (The National Academies Press, 2006)
Each year, more than 33 million Americans receive health care for mental or substance-use conditions, or both. Together, mental and substance-use illnesses are the leading cause of death and disability for women, the highest for men ages 15-44, and the second highest for all men. Effective treatments exist, but services are frequently fragmented and, as with general health care, there are barriers that prevent many from receiving these treatments as designed or at all. The consequences of this are serious—for these individuals and their families; their employers and the workforce; for the nation's economy; as well as the education, welfare, and justice systems. Improving the Quality of Health Care for Mental and Substance-Use Conditions examines the distinctive characteristics of health care for mental and substance-use conditions, including payment, benefit coverage, and regulatory issues, as well as health care organization and delivery issues. This new volume in the Quality Chasm series puts forth an agenda for improving the quality of this care based on this analysis. Patients and their families, primary health care providers, specialty mental health and substance-use treatment providers, health care organizations, health plans, purchasers of group health care, and all involved in health care for mental and substance–use conditions will benefit from this guide to achieving better care.
Keywords: Health and Medicine

Framing Opioid Prescribing Guidelines for Acute Pain: Developing the Evidence - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The opioid overdose epidemic combined with the need to reduce the burden of acute pain poses a public health challenge. To address how evidence-based clinical practice guidelines for prescribing opioids for acute pain might help meet this challenge, Framing Opioid Prescribing Guidelines for Acute Pain: Developing the Evidence develops a framework to evaluate existing clinical practice guidelines for prescribing opioids for acute pain indications, recommends indications for which new evidence-based guidelines should be developed, and recommends a future research agenda to inform and enable specialty organizations to develop and disseminate evidence-based clinical practice guidelines for prescribing opioids to treat acute pain indications. The recommendations of this study will assist professional societies, health care organizations, and local, state, and national agencies to develop clinical practice guidelines for opioid prescribing for acute pain. Such a framework could inform the development of opioid prescribing guidelines and ensure systematic and standardized methods for evaluating evidence, translating knowledge, and formulating recommendations for practice.
Keywords: Health and Medicine

Collaboration Between Health Care and Public Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2016)
On February 5, 2015, the Institute of Medicine Roundtable on Population Health Improvement hosted a workshop to explore the relationship between public health and health care, including opportunities, challenges, and practical lessons. The workshop was convened in partnership with the Association of State and Territorial Health Officials (ASTHO)-Supported Primary Care and Public Health Collaborative. Organized in response to the 2012 IOM report Primary Care and Public Health: Exploring Integration to Improve Population Health, this workshop focused on current issues at the interface of public health and health care, including opportunities presented by and lessons learned from the Centers for Medicaid and Medicare Services State Innovation Models program. The workshop featured presentations on several dimensions of the public health-health care relationship. Collaboration Between Health Care and Public Health summarizes the presentations and discussion of the event.
Keywords: Health and Medicine

The Role of Nonpharmacological Approaches to Pain Management: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Pain is a leading cause of disability globally. The dramatic increase in opioid prescriptions within the past decade in the United States has contributed to the opioid epidemic the country currently faces, magnifying the need for longer term solutions to treat pain. The substantial burden of pain and the ongoing opioid crisis have attracted increased attention in medical and public policy communities, resulting in a revolution in thinking about how pain is managed. This new thinking acknowledges the complexity and biopsychosocial nature of the pain experience and the need for multifaceted pain management approaches with both pharmacological and nonpharmacological therapies.
Keywords: Health and Medicine

Integrating Responses at the Intersection of Opioid Use Disorder and Infectious Disease Epidemics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
According to the Centers for Disease Control and Prevention (CDC), 115 Americans die each day from an opioid overdose, which averages one death every 12.5 minutes. Between 1999 and 2016, the number of drug overdoses catapulted by 300 percent, with injection drug use increasing by 93 percent between 2004 and 2014 and opioid-related hospital admissions increasing by 58 percent over the past decade. And an inexorable sequela of the opioid epidemic is the spread of infectious diseases. To address these infectious disease consequences of the opioid crisis, a public workshop titled Integrating Infectious Disease Considerations with Response to the Opioid Epidemic was convened on March 12 and 13, 2018, by the National Academies of Sciences, Engineering, and Medicine. Participants discussed strategies to prevent and treat infections in people who inject drugs, especially ways to work efficiently though the existing public health and medical systems. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Relieving Pain in America: A Blueprint for Transforming Prevention, Care, Education, and Research - Institute of Medicine (The National Academies Press, 2011)
Chronic pain costs the nation up to $635 billion each year in medical treatment and lost productivity. The 2010 Patient Protection and Affordable Care Act required the Department of Health and Human Services (HHS) to enlist the Institute of Medicine (IOM) in examining pain as a public health problem. In this report, the IOM offers a blueprint for action in transforming prevention, care, education, and research, with the goal of providing relief for people with pain in America. To reach the vast multitude of people with various types of pain, the nation must adopt a population-level prevention and management strategy. The IOM recommends that HHS develop a comprehensive plan with specific goals, actions, and timeframes. Better data are needed to help shape efforts, especially on the groups of people currently underdiagnosed and undertreated, and the IOM encourages federal and state agencies and private organizations to accelerate the collection of data on pain incidence, prevalence, and treatments. Because pain varies from patient to patient, healthcare providers should increasingly aim at tailoring pain care to each person's experience, and self-management of pain should be promoted. In addition, because there are major gaps in knowledge about pain across health care and society alike, the IOM recommends that federal agencies and other stakeholders redesign education programs to bridge these gaps. Pain is a major driver for visits to physicians, a major reason for taking medications, a major cause of disability, and a key factor in quality of life and productivity. Given the burden of pain in human lives, dollars, and social consequences, relieving pain should be a national priority.
Keywords: Health and Medicine

Living Well with Chronic Illness: A Call for Public Health Action - Institute of Medicine (The National Academies Press, 2012)
In the United States, chronic diseases currently account for 70 percent of all deaths, and close to 48 million Americans report a disability related to a chronic condition. Today, about one in four Americans have multiple diseases and the prevalence and burden of chronic disease in the elderly and racial/ethnic minorities are notably disproportionate. Chronic disease has now emerged as a major public health problem and it threatens not only population health, but our social and economic welfare. Living Well with Chronic Disease identifies the population-based public health actions that can help reduce disability and improve functioning and quality of life among individuals who are at risk of developing a chronic disease and those with one or more diseases. The book recommends that all major federally funded programmatic and research initiatives in health include an evaluation on health-related quality of life and functional status. Also, the book recommends increasing support for implementation research on how to disseminate effective longterm lifestyle interventions in community-based settings that improve living well with chronic disease. Living Well with Chronic Disease uses three frameworks and considers diseases such as heart disease and stroke, diabetes, depression, and respiratory problems. The book's recommendations will inform policy makers concerned with health reform in public- and private-sectors and also managers of communitybased and public-health intervention programs, private and public research funders, and patients living with one or more chronic conditions.
Keywords: Health and Medicine

The Health Effects of Cannabis and Cannabinoids: The Current State of Evidence and Recommendations for Research - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Significant changes have taken place in the policy landscape surrounding cannabis legalization, production, and use. During the past 20 years, 25 states and the District of Columbia have legalized cannabis and/or cannabidiol (a component of cannabis) for medical conditions or retail sales at the state level and 4 states have legalized both the medical and recreational use of cannabis. These landmark changes in policy have impacted cannabis use patterns and perceived levels of risk.
Keywords: Health and Medicine

Substance Use Disorders in the U.S. Armed Forces - Institute of Medicine (The National Academies Press, 2013)
Problems stemming from the misuse and abuse of alcohol and other drugs are by no means a new phenomenon, although the face of the issues has changed in recent years. National trends indicate substantial increases in the abuse of prescription medications. These increases are particularly prominent within the military, a population that also continues to experience long-standing issues with alcohol abuse. The problem of substance abuse within the military has come under new scrutiny in the context of the two concurrent wars in which the United States has been engaged during the past decade—in Afghanistan (Operation Enduring Freedom) and Iraq (Operation Iraqi Freedom and Operation New Dawn). Increasing rates of alcohol and other drug misuse adversely affect military readiness, family readiness, and safety, thereby posing a significant public health problem for the Department of Defense (DoD). To better understand this problem, DoD requested that the Institute of Medicine (IOM) assess the adequacy of current protocols in place across DoD and the different branches of the military pertaining to the prevention, screening, diagnosis, and treatment of substance use disorders (SUDs). Substance Use Disorders in the U.S. Armed Forces reviews the IOM's task of assessing access to SUD care for service members, members of the National Guard and Reserves, and military dependents, as well as the education and credentialing of SUD care providers, and offers specific recommendations to DoD on where and how improvements in these areas could be made.
Keywords: Health and Medicine; Conflict and Security Issues

Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Estimates indicate that as many as 1 in 4 Americans will experience a mental health problem or will misuse alcohol or drugs in their lifetimes. These disorders are among the most highly stigmatized health conditions in the United States, and they remain barriers to full participation in society in areas as basic as education, housing, and employment. Improving the lives of people with mental health and substance abuse disorders has been a priority in the United States for more than 50 years. The Community Mental Health Act of 1963 is considered a major turning point in America's efforts to improve behavioral healthcare. It ushered in an era of optimism and hope and laid the groundwork for the consumer movement and new models of recovery. The consumer movement gave voice to people with mental and substance use disorders and brought their perspectives and experience into national discussions about mental health. However over the same 50-year period, positive change in American public attitudes and beliefs about mental and substance use disorders has lagged behind these advances. Stigma is a complex social phenomenon based on a relationship between an attribute and a stereotype that assigns undesirable labels, qualities, and behaviors to a person with that attribute. Labeled individuals are then socially devalued, which leads to inequality and discrimination. This report contributes to national efforts to understand and change attitudes, beliefs and behaviors that can lead to stigma and discrimination. Changing stigma in a lasting way will require coordinated efforts, which are based on the best possible evidence, supported at the national level with multiyear funding, and planned and implemented by an effective coalition of representative stakeholders. Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change explores stigma and discrimination faced by individuals with mental or substance use disorders and recommends effective strategies for reducing stigma and encouraging people to seek treatment and other supportive services. It offers a set of conclusions and recommendations about successful stigma change strategies and the research needed to inform and evaluate these efforts in the United States.
Keywords: Behavioral and Social Sciences; Health and Medicine

Measuring Recovery from Substance Use or Mental Disorders: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In February 2016, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore options for expanding the Substance Abuse and Mental Health Services Administration's (SAMHSA) behavioral health data collections to include measures of recovery from substance use and mental disorder. Participants discussed options for collecting data and producing estimates of recovery from substance use and mental disorders, including available measures and associated possible data collection mechanisms. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Behavioral and Social Sciences; Surveys and Statistics